Analyzing the Impact of Work Motivation and Discipline on Employee Performance at Badan Kesatuan Bangsa dan Politik Kuala Kapuas - Shintia, Novi; Renaldi, Renaldi; Mutammimah, Heppy; Amelia, Rini (Journal of Business Management and Economic Development, 2025)
This study aimed to explore the effect of work motivation and discipline on employee performance at Badan Kesatuan Bangsa dan Politik Kuala Kapuas. This study was a quantitative study using a survey approach. Forty respondents participated in this study. The collected data through a questionnaire was analyzed using multiple linear regression via SPSS. The results showed that work motivation had a minimal and statistically insignificant effect on employee performance, though it contributes slightly, reflecting the complex nature of its impact. In contrast, work discipline had a significant and dominant effect, emphasizing the importance of adherence to organizational rules and accountability in enhancing productivity. Furthermore, the combined analysis revealed that work motivation and discipline significantly influenced employee performance, contributing 33.6% to its variability. These findings emphasize the importance of fostering motivation and discipline as complementary strategies for optimizing employee contributions and achieving organizational success.